Effect of different amounts of feeds on growth and production of fishes in pond polyculture - Sultana, S; Rahman, MS; Jackshay, KA; Hasan, K (International Journal of Agricultural Research, Innovation and Technology, 2021)
An experiment was carried out to evaluate the effects of different amounts of supplementary feeds on growth and production of fishes in polyculture where four different species such as rui (Labeo rohita), mrigal (Cirrhinus mrigala), common carp (Cyprinus carpio) and tilapia (Oreochromis niloticus) were cultured in 6 ponds under three treatments, each with two replications. Eighty fish per decimal were stocked along with the stocking ratio of 1:1:1:1 in all the treatments. Supplementary feeds of rice bran and wheat bran (1:1), at the amount of 5% of body weight were applied in 2 ponds (treatment I) as well as at the amount of 3% of body weight were used in 2 ponds (treatment II) and 2 ponds (treatment III) were as control where no supplementary feed was used. Urea and T.S.P were applied fortnightly at the rate of 60 g decimal-1 and 90 g decimal-1, respectively under all treatments. Physico-chemical and biological factors such as air and water temperature, transparency, rainfall, pH, dissolved oxygen, free CO2, total alkalinity, PO4-P and NO3-N, phytoplankton and zooplankton were studied fortnightly and the limnological conditions were more or less similar in the experimental ponds under three treatments. The calculated gross and net fish productions of fishes under treatment I, treatment II and treatment III were 8.87 and 7.33 ton ha-1 yr-1, 7.12 and 5.58 ton ha-1 yr-1 and 4.69 and 3.16 ton ha-1 yr-1, respectively. Percent increased of net fish productions of treatment I and treatment II were 231.97% and 176.59% higher than that of treatment III (control). The present study reveals that supplementary feeding in fish culture should be done along with fertilization because supplementary feeds are very important to enhance growth of fishes significantly. Int. J. Agril. Res. Innov. Tech. 10(2): 128-136, December 2020